Ethnographies of Islam : ritual performances and everyday practices - Dupret, Baudouin; Aga Khan University. Institute for the Study of Muslim Civilisations (Edinburgh : Edinburgh University Press, 2012)
This comparative approach to the various uses of the ethnographic method in research about Islam in anthropology and other social sciences is particularly relevant in the current climate. Political discourses and stereotypical media portrayals of Islam as a monolithic civilisation have prevented the emergence of cultural pluralism and individual freedom. Such discourses are countered by the contributors who show the diversity and plurality of Muslim societies and promote a reflection on how the ethnographic method allows the description, representation and analysis of the social and cultural complexity of Muslim societies in the discourse of anthropology.--provided by publisher.
Part I : performing rituals -- Part II : contextualising interactions -- Part III : the ethnography of history.
Published in association with the Aga Khan University, Institute for the Study of Muslim Civilisations--t.p.
Includes index.
Keywords: Religious life -- Islam; Islam -- Customs and practices; Rites and ceremonies -- Islamic countries; Islam -- Rituals; Pluralism -- Religious aspects -- Islam; Muslim diaspora; Muslims -- Ethnic identity; Islam and civil society